Estudio de los mecanismos que regulan la activación de linfocitos Tyd inducida por diferentes agonistas : caracterización del rol inmunomodulador de los neutrófilos - Towstyka, Nadia Yasmín (2017)
In this study, we evaluated the activation of human blood yd T cells stimulated by anti-CD3 antibodies, phosphoantigens and monosodium urate crystals (MSU). Also we investigated the role of neutrophils during the activation of yd T cells. We found that the up-regulation of CD69 expression, and the production of IFN-y and TNF-a induced by anti-CD3 antibodies were potentiated by neutrophils. The inhibition of serine proteases prevented the potentiation of yd T cell activation induced by neutrophils. Moreover, the addition of elastase, cathepsin G and proteinase 3 to yd T cell culture increased their stimulation. We demonstrated that the effect of serine proteases on yd T cells was mediated through the proteases-activated receptor, PAR1. On the other hand, this work demonstrated that MSU crystals activated yd T cells by increasing the expression of CD25 and CD69, and the production of IFN-y and TNF-a. The stimulatory effect of MSU crystals was dependent on Spleen tyrosine kinase Syk, since the treatment of cells with the inhibitor GS-9973 decreased the stimulation of yd T cells. Moreover, the treatment of cells with MSU crystals triggered the phosphorylation of Syk. Also we observed that neutrophils exerted an inhibitory effect on yd T cells activated by MSU crystals.